2002
DOI: 10.1177/088541220201700103
|View full text |Cite
|
Sign up to set email alerts
|

Later-Life Migration in the United States: A Review of Recent Research

Abstract: This bibliography summarizes the most important recent literature on elderly migration and retirement migration in the U.S. and Canada, providing an interdisciplinary review of articles published between January 1990 and December 2000. It describes and evaluates 232 studies dealing with migration theory and methods, the determinants of later-life mobility, patterns of migration, destination choice, consequences of migration, local and regional development, seasonal migration, return migration, and related topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
90
1
14

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 189 publications
(209 reference statements)
1
90
1
14
Order By: Relevance
“…Gerontological research suggests that individual-level variables and life course events influence the likelihood of moving in later life. For instance, research has shown that residential mobility in older age is more prevalent among retirees than those still employed, in younger than older old age, among those with higher levels of education or economic resources, in those with health concerns or disability, and those in urban versus rural areas (Sergeant & Ekerdt, 2008;Taylor, Morin, Cohn, & Wang, 2008;Walters, 2002). Less is known about the influence of neighborhood conditions on residential mobility in later life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gerontological research suggests that individual-level variables and life course events influence the likelihood of moving in later life. For instance, research has shown that residential mobility in older age is more prevalent among retirees than those still employed, in younger than older old age, among those with higher levels of education or economic resources, in those with health concerns or disability, and those in urban versus rural areas (Sergeant & Ekerdt, 2008;Taylor, Morin, Cohn, & Wang, 2008;Walters, 2002). Less is known about the influence of neighborhood conditions on residential mobility in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the influence of neighborhood conditions on residential mobility in later life. Evidence suggests that older adults move to avoid high seasonal temperature variation and high tax rates (Walters, 2002), but the effects of neighborhood disadvantage are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers suggest that life stage does not fully explain later life (Oswald, Schilling, Hans-Werner, & Karen 2002) [9]; Walters (2000) [6] introduced the concept of intention and enabling attributes. Intention is to take advantage of an amenity.…”
mentioning
confidence: 99%
“…Walters submits that life course studies of elderly migration focus on three primary goals: 1) identifying the events most closely associated with geographic mobility in later life, 2) classifying and describing the individuals most likely to move in response to each event and 3) identifying and assessing the place characteristics most often associated with the mobility of each migrant (Walters 2002, p. 39) [6]. Litwak and Longino (1987) [7] proposed a developmental subcategory of the life course model.…”
mentioning
confidence: 99%
See 1 more Smart Citation